Oral hygiene and gingival health among adult population (21-80) years in Thamar-Yemen - Faraed D Salman; Rayia J Al-Naimi; Ghada Dh Al-Sayagh (University of Mosul, College of Dentistry, 2004)
The aim of the study is to evaluate the oral hygiene and gingival health and to find if there is any variation between sex and age groups among adults aged 21-80 years in Thamar-Yemen. A sample of 224 individuals aged 21-80 years (177 males and 47 females) were examined using plaque index by Silness and Löe (1964) and gingival index by Löe and Silness (1963). The results showed that the mean plaque score for the total sample was 1.15; the plaque index was increasing with age significantly. Males reported higher means than females with statistical significant difference in the 3rd, and 5th age groups; while at the 4th age group the females rep-orted significantly higher plaque scores than males. The mean gingival score for the total sample was low (0.84) and it was increa-sing with age significantly. The mean gin-gival score was slightly better in males than females with statistical significant difference in all age groups except the 5th age group where the females showed bet-ter gingival health. Therefore, the objective of dental health education to those adults is to imp-rove the effectiveness of oral hygiene pra-ctice by tooth brushing and interdental aids.